INDUKSI KALUS DENGAN 2,4D DAN BAP PADA EKSPLAN DAUN VEGETATIF DAN GENERATIF TEMPUYUNG (Sonchus arvensis L.) - Shilfiana - Rahayu; Suharyanto Suharyanto (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
Tempuyung (Sonchus arvensis L.) is a plant that has many benefits and medicinal potencial. This plant is contain high flavonoids and terpenoids. The propagation of this plant is very important to do to provide medicinal ingridients on a prefab scale and to produce materials that have a high compound content. The tissue culture is one of the fastest ways in plant propagation and can increase the content of secondary metabolites in plants. The method to produce high compounds and produce somatic embryos in large quantities can be through callus culture. The research aim was to find the effect of 2,4D and BAP hormones and leaf explant variations on the growth tempuyung callus. In this research, a combination of 2,4D (0; 0.5; 1 ppm) and BAP (0; 0.5; 1 ppm) hormone was used in inducing callus, and explants used in this research were vegetative leaves and generative leaves of tempuyung. The results of this study stated that callus was produced within 10-14 days, with the friable callus texture and yellow in color. Vegetative leaf explants initiate callus faster than generative leaves. Other results showed that the best combination in callus production was BAP 0.5 ppm and 2.4D 1 ppm, and the most optimal leaf explants in producing callus were found in vegetative leaf explants